Intersigmoid Hernia: A Forgotten Diagnosis—A Systematic Review of the Literature over Anatomical, Diagnostic, Surgical, and Medicolegal Aspects. (1st June 2020) - Chiarini, Stella; Ruscelli, Paolo; Cirocchi, Roberto; D'Andrea, Vito; Sensi, Beatrice; Santoro, Alberto; Corsi, Alessia; Zepponi, Federico; Fedeli, Piergiorgio; Gioia, Sara
Abstract : Introduction . Intersigmoid hernia is a hernia of the small bowel into the intersigmoid fossa. It is well known to be a rare condition. Recent reports reveal that the preoperative differentiation of intersigmoid hernias is difficult and the diagnosis is often confirmed during the laparotomic exploration. Due to the vague clinical manifestation in most cases, the surgical treatment is frequently delayed. Materials and Methods . In this study, we systematically reviewed the literature up to 2019 covering 114 studies and 124 patients with an intersigmoid hernia. The purpose of this work is to improve the understanding of the anatomical aspects, clinical presentation, diagnosis, and treatment of intersigmoid hernia so as to assist the preoperative differentiation of these hernias when presented as acute abdomen in the emergency department. Results . The diameter of the intersigmoid recess was reported with mean 2.65 cm (range 1–10 cm, SD 1.15 cm) and the length of the incarcerated small intestine was between 3 cm (min) and 150 cm (max): mean 25.25 cm, SD 35.04 cm. The diameter of the sigmoid recess was greater in patients who underwent resection due to strangulation (mean 3.31 cm, SD 1.53 cm) compared to those who underwent only reduction of the hernia (mean 2.35 cm, SD 0.74 cm). The time from onset to operation was less in patients undergoing resection surgery due to throttling (mean 3.03 days, SD 3.01 days) compared to those who underwent only a reduction of hernia incarceration (mean 8.49 days, SD 6.83 days). Conclusion . Intersigmoid hernia is often a forgotten diagnosis and a clinical challange due to its anatomical characteristics.